2020
DOI: 10.1371/journal.pone.0239100
|View full text |Cite
|
Sign up to set email alerts
|

Impact of left ventricular ejection fraction on the effect of renin-angiotensin system blockers after an episode of acute heart failure: From the KCHF Registry

Abstract: Objective This observational study aimed to examine the prognostic association of angiotensin-converting enzyme inhibitors (ACE-I)/angiotensin receptor blockers (ARB) in different left ventricular ejection fraction (LVEF) categories. Methods In 3717 patients enrolled in the KCHF Registry, a multicentre registry including consecutive patients hospitalized for acute heart failure (HF), we assessed patient characteristics and association between ACE-I/ARB and clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Such studies are usually conducted prospectively, although the disease registries or databases themselves are sometimes used for retrospective secondary analysis. In the identified studies, three Japanese registries/databases were used by researchers of different studies: All-Japan Utstein Registry [ 22 , 23 ], National Database of Rheumatic Diseases by iR-net (Division of Rheumatology, Immunologic Disorder Network, National Hospital Organization) in Japan (NinJa) [ 24 , 25 ], and Kyoto Congestive Heart Failure (KCHF) Registry [ 26 , 27 ]. In addition, although our focus was on studies conducted in Japan, we identified seven registry studies conducted by using the Surveillance, Epidemiology, and End Results (SEER) program of the US National Cancer Institute.…”
Section: Resultsmentioning
confidence: 99%
“…Such studies are usually conducted prospectively, although the disease registries or databases themselves are sometimes used for retrospective secondary analysis. In the identified studies, three Japanese registries/databases were used by researchers of different studies: All-Japan Utstein Registry [ 22 , 23 ], National Database of Rheumatic Diseases by iR-net (Division of Rheumatology, Immunologic Disorder Network, National Hospital Organization) in Japan (NinJa) [ 24 , 25 ], and Kyoto Congestive Heart Failure (KCHF) Registry [ 26 , 27 ]. In addition, although our focus was on studies conducted in Japan, we identified seven registry studies conducted by using the Surveillance, Epidemiology, and End Results (SEER) program of the US National Cancer Institute.…”
Section: Resultsmentioning
confidence: 99%
“…Such studies are usually conducted prospectively, although the disease registries or databases themselves are sometimes used for retrospective secondary analysis. In the identi ed studies, three Japanese registries/databases were used by researchers of different studies: All-Japan Utstein Registry 16,17 , National Database of Rheumatic Diseases in Japan (NinJa) 18,19 , and Kyoto Congestive Heart Failure (KCHF) Registry 20,21 . In addition, although our focus was on studies conducted in Japan, we identi ed seven registry studies conducted by using the Surveillance, Epidemiology, and End Results (SEER) program of the US National Cancer Institute.…”
Section: Resultsmentioning
confidence: 99%